2020
DOI: 10.1158/1055-9965.epi-19-0352
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Coverage, Employment Status, and Financial Well-Being of Young Women Diagnosed with Breast Cancer

Abstract: Background: The economic cost of breast cancer is a major personal and public health problem in the United States. This study aims to evaluate the insurance, employment, and financial experiences of young female breast cancer survivors and to assess factors associated with financial decline.Methods: We recruited 830 women under 40 years of age diagnosed with breast cancer between January 2013 and December 2014. The study population was identified through California, Florida, Georgia, and North Carolina populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Work ability reflects a complex interaction of individual and occupational factors 21 . Individual factors associated with employment outcomes may include education, income, marital status, race, rurality and age 13,16,22‐25 . Occupational factors may include physical, cognitive, and interpersonal work demands, company size, coworker support, and flexibility of work hours and work tasks 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work ability reflects a complex interaction of individual and occupational factors 21 . Individual factors associated with employment outcomes may include education, income, marital status, race, rurality and age 13,16,22‐25 . Occupational factors may include physical, cognitive, and interpersonal work demands, company size, coworker support, and flexibility of work hours and work tasks 26 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature often focuses on employment as a simple dichotomous outcome (employed vs unemployed); the variations in employment laws by country may also confound outcomes 21,28 . Furthermore, the published literature often assesses survivors in cross‐sectional surveys: data suggest that difficulties seen at 6 to 12 months posttreatment predict difficulty at later time points, 13 but the inclusion of individuals who are years removed from diagnosis may increase response bias 17,22,23 …”
Section: Introductionmentioning
confidence: 99%
“… 25 Patients who are un‐ or underemployed may lack benefits such as health insurance, paid sick leave, and disability insurance, which may worsen their financial status and make it more difficult to attend medical appointments in a timely manner. 33 , 56 , 57 …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown the adverse effects of breast cancer on employment but have not empirically assessed the employment effects of a breast cancer screening program [ 9 13 ]. Such employment effects for breast cancer survivors depend on how the program affects their employability.…”
Section: Introductionmentioning
confidence: 99%